Education and space for mobile lives: A joint studio experiment in Ayvalık - Çakıcı, Fatma Zehra; Örmecioğlu, Hilal Tuğba (Journal of Human Sciences, 2017)
While tragic news of hundreds of refugees, who are trying to reach to Europe through illegal and dangerous routes as they are running from violence of war, rose to rank high on the world agenda, Turkey experience the social, economic and cultural trauma of refugees expressed in millions. Education is one of the critical aspects of the problem, not only as formal education of children but life-saving support for adults who had to adapt themselves to temporary conditions and uncertain future scenarios. With these concerns in mind, the aim of this paper is to convey the process and results of 2015-2016 spring semester conjoint studio of Atatürk University with METU on “education for life-on-move”. Ayvalık is chosen as the project site since it is one of the important destinations of the refugees on their way to Lesbos. Besides, the area is a historic refugee settlement, hosted many different communities, including Greek, Bosnian, Turks etc. for ages. Hence, it developed a pluralist identity and cosmopolitan culture.